GEOSPATIAL ASSESSMENT OF URBAN SERVICE ACCESSIBILITY FOR SMART CITY PLANNING: A CASE STUDY OF DAVANAGERE CITY, KARNATAKA, INDIA - Yashvanth S S; Syed Ashfaq Ahmed; Madeeha Arif (International Educational Journal of Science and Engineering, 2026)
This study investigates the spatial accessibility of essential public service facilities in Davanagere city through the application of geospatial techniques. The analysis considers three critical categories of urban services, namely healthcare facilities, educational institutions, and fire stations, in order to examine their spatial distribution and accessibility within the municipal boundary. A Geographic Information System (GIS) based buffer approach was adopted to delineate service coverage areas, employing standard threshold distances of 1 km for hospitals, 500 m for educational facilities, and 2 km for fire stations. The individual service buffers were subsequently integrated to produce a composite accessibility layer, and service-deficient zones were identified using spatial overlay analysis. The results indicate that approximately 47.44% of the total urban area is adequately served by at least one essential facility, where as 52.56% of the area remains underserved. The spatial patterns reveal a pronounced concentration of services in the central parts of the city, while peripheral zones exhibit notable accessibility deficits. These findings highlight the presence of spatial disparities in infrastructure distribution and underline the necessity for more balanced urban planning interventions. The study demonstrates the capability of GIS based spatial analysis in systematically identifying service gaps and supporting evidence based decision making. The outcomes provide valuable insights for urban planners and policymakers to enhance service accessibility, optimize infrastructure placement, and promote equitable and sustainable urban development within the framework of smart city initiatives.